The Effect Of Customer Satisfaction As A Mediating Variable On Muslim Fashion Customers In Surakarta - Dinda Wulan Andari; Muhammad Sholahuddin (Jurnal Ekonomi Bisnis Manajemen Prima, 2023)
The desire and need for Muslim clothing is increasing, companies engaged in fashion are competing to make the best Muslim products and in accordance with trends. This study generally aims to examine customer satisfaction of Muslim fashion products in Surakarta. Specifically, this study aims to analyze the effect of product quality, price, and promotion on customer loyalty through customer satisfaction as a mediating variable for Muslim fashion customers in Surakarta. Respondents in this study were 180 people through an online survey. The sampling technique used non-probability sampling with purposive sampling method. Validity and reliability tests using smart PLS analysis on the outer model. Hypothesis testing using smartPLS inner model output. The results of data analysis show that this research instrument has good validity and reliability. Product quality, promotion and price and have a direct effect on customer loyalty. Customer satisfaction is able to mediate the relationship between product quality and promotion to customer loyalty, but customer satisfaction is not able to mediate the price relationship to customer loyalty. This article has the potential to make an important contribution to the development of the fashion subsector, especially Muslim fashion in Indonesia, by presenting new and relevant information.